Pelatihan Pembuatan Virgin Coconut Oil (VCO) Di Sekolah Metta Maitreya Pekanabaru - Irawati Irawati; Hosan Hosan; Dharmaji Chowmas; Rida Jelita; Yadi Sutikno; Mega Ratna Sari; Jali; Hari Sutiawan (JPPkM: Jurnal Pengabdian dan Pemberdayaan kepada Masyarakat, 2026)
This Community Service Activity aims to provide training to educators and the community around the Metta Maitreya Pekanbaru School on how to make Virgin Coconut Oil (VCO) independently and hygienically. Virgin Coconut Oil is a natural product that has many benefits, both for health and beauty, and has the potential to become an entrepreneurial product with economic value. This training was carried out through lectures, demonstrations, and direct practice by participants. The results of the activity showed that the training went smoothly and succeeded in increasing the knowledge and skills of participants in processing coconuts into VCO. In addition, this activity also encouraged the spirit of entrepreneurship and the use of natural products among the community. Thus, this training provides a positive contribution to community empowerment and improving skills based on local potential.